Дослідження фокусувальних властивостей градієнтної лінзи люнебурга - Цівінський, В. М. (ХНУРЕ, 2023)
This work is devoted to investigation of the focusing properties of gradient Luneburg lens. The analysis of the gradient lens is performed using a three-dimensional computer model. Incidence of the light ray bundle on the gradient spherical lens is considered. Patterns of the ray trajectories are calculated at both outside and inside gradient lens. Effect of the focal shift parameter on trajectories pattern is investigated. Developed computer model can be used for investigation of different type of gradient lenses